2013
DOI: 10.1002/ajmg.b.32161
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of schizophrenia: Genetic and symptomatic factors

Abstract: Schizophrenia may have etiological heterogeneity, and may reflect common symptomatology caused by many genetic and environmental factors. In this review, we show the potential existence of heterogeneity in schizophrenia based on the results of our previous studies. In our study of the NOTCH4 gene, there were no significant associations between any single nucleotide polymorphisms (SNPs) of NOTCH4 and schizophrenia. However, exploratory analyses suggested that the SNP, rs3134928 may be associated with early-onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…We have recently reported a cumulative contribution of multiple protein sequence altering inherited rare variants in genes from nurodevelopmental pathways which has provided plausible genetic explanation for disease transmission and also supported the oligogenic hypothesis (John et al, 2019). Finally, considering the highly genetically heterogeneous nature of the disease (Beckmann and Franzek, 2000;Rees et al, 2015;Takahashi, 2013), such risk conferring genes may fall in a few different disease relevant pathways with their number and combinations varying across different families.…”
Section: Introductionsupporting
confidence: 54%
“…We have recently reported a cumulative contribution of multiple protein sequence altering inherited rare variants in genes from nurodevelopmental pathways which has provided plausible genetic explanation for disease transmission and also supported the oligogenic hypothesis (John et al, 2019). Finally, considering the highly genetically heterogeneous nature of the disease (Beckmann and Franzek, 2000;Rees et al, 2015;Takahashi, 2013), such risk conferring genes may fall in a few different disease relevant pathways with their number and combinations varying across different families.…”
Section: Introductionsupporting
confidence: 54%
“…10,11 Using supervised pattern recognition methods, including soft independent modelling of class analogy (SIMCA), we found that deficit schizophrenia is a qualitatively distinct class or nosological entity modelled and defined by neuroimmune (IgA/IgM responses directed to TRYCATs) and cognitive (episodic and semantic memory) features coupled or not with negative symptoms. 16 While these findings provide further support to the notion that schizophrenia is not an unitary disorder, 3,17 the status of nondeficit schizophrenia was not clear as it showed a large overlap not only with healthy controls but also with deficit patients. In this respect, Braff et al 18 ascertained that also latent class and genetic studies support the deficit subtype of schizophrenia, but that the DSM-5 classification would not be enhanced by adding this subtype without a valid definition of the nondeficit subtype.…”
Section: Introductionmentioning
confidence: 83%
“…SCZ is highly heritable severe mental disorder with clinically heterogeneous symptoms (Picardi et al, 2012; Takahashi, 2013) and different risk factors (Mäki et al, 2005; Serafini et al, 2012). Several lines of evidence point to neurodevelopment as playing a primary role in etiology of the disease (Weinberger, 1987; Raedler et al, 1998; Lewis and Levitt, 2002).…”
Section: Discussionmentioning
confidence: 99%